Corticotropin releasing factor in the nucleus basalis of Meynert impairs attentional performance and reduces levels of glutamate and taurine in male and female rats - Eck, S. R.; Kokras, N; Wicks, B.; Baltimas, P.; Hall, A.; van Bendegem, N.; Salvatore, M.; Cohen, S. R.; Bergmann, J.; Ceretti, A.; Parikh, V.; Dalla, C; et al. (Neuropharmacology, 2022)
Psychiatric disorders that are characterized by impairments in sustained attention, including attention deficit hyperactivity disorder (ADHD), post-traumatic stress disorder (PTSD), and major depression are also sensitive to exacerbation by stress. Sustained attention relies on cholinergic and non-cholinergic projections from the nucleus basalis of Meynert (NBM) in the basal forebrain to the medial prefrontal cortex (mPFC). We have previously shown that central administration of the stress neuropeptide corticotropin releasing factor (CRF) impairs performance on the sustained attention task (SAT) in adult male and female rats. The present study investigated whether this effect was mediated by CRF's action in the NBM. Rats were administered CRF in the NBM and subsequent SAT performance was measured. A high dose of CRF (100 ng) significantly impaired performance on non-signaled events across sex. Because performance on non-signaled events is believed to depend on non-cholinergic (i.e., GABA and glutamate) signaling, high performance liquid chromatography was used to quantify amino acid levels in the NBM and mPFC. We found females have higher levels of glutamate, glutamine, GABA glycine, and alanine in the NBM than males. Importantly, CRF in the NBM led to a local decrease of taurine and several amino acids involved in glutamate synthesis in males and females, changes which may mediate the CRF-induced SAT performance deficit. Together these studies suggest that CRF regulation of amino acids in the NMB contributes to stress-induced attention deficits.
Keywords: *Basal Nucleus of Meynert; *Corticotropin-Releasing Hormone/metabolism; Animals; Attention; Basal forebrain; Cognition; Female; gamma-Aminobutyric Acid/metabolism; Glutamate; Glutamic Acid/metabolism; Male; Rats; stress; Taurine/metabolism